SAXS study of monodispersed silica nanospheres obtained by an amino acid route - Bertholdo, Roberto [UNESP]; dos Reis, Flavia V. E. [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP] (Elsevier B.V., 2010)
Spherical silica nanoparticles were prepared using a basic amino acid catalysis route and the kinetics of the particles growth was investigated by small angle X-ray scattering (SAXS). L-arginine was used in the polar aqueous phase as the basic catalyst whereas the tetraethylorthosilicate (TEOS) was dissolved in the cyclohexane oil phase as the silicate monomer source. The SAXS measurements were taken in the aqueous phase at different reaction times. A high degree of monodispersity was clearly evidenced for the spherical nanoparticles as a result of the pronounced high-order oscillations observed in the SAXS curves. The SAXS data show that the particles number density remains unchanged since both the particle size as well as the volume fraction gradually increase. This process was discussed based on a reaction-controlled addition of monomer species at the surface of the growing particles. Consequently, the monodispersed spherical nanoparticles radius can as such be finely tuned from 7 to 12 nm by varying the reaction time. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Silica nanoparticles; Monodispersed spheres; Amino acid; SAXS